Microstructural aspects of wear behaviour of TiC coated low alloy steel - Md Idriss, A. N.; Maleque, Md. Abdul; Yaacob, Iskandar Idris; Md Nasir, Ramdziah; Mridha, Shahjahan; Baker, T. N. (Taylor & Francis, 2016)
A comparison of the room temperature wear behaviour of untreated low alloy steel surfaces with those containing TiC powders was conducted against an alumina ball. The coefficient of friction, the wear rate and the severity of the damage on the surface were assessed. Incorporation of powders produced a hardness 2.6 times greater and a wear rate 21 times less than the untreated steel. Friction from the third body abrasion and protruding carbides of the processed steel resulted in mild wear with a steady state coefficient friction of 0.4. Both samples showed surface chemical reactivity with the environment as a result of the generation of flash temperature producing an oxide layer, which influenced wear.